Round Table: «Climate Change and Extractive Industries: The Challenges for a Sustainable Economic Development» - Abanto Cabanillas, Alicia (2014)
The arrival of the 20th session of the Conference of the Parties (COP 20) brings an atmosphere of reflection about climate change. Thus, this event will aim to generate debate about the role to be fulfilled by the Peruvian State in the context of this Conference; and, in general, mitigation measures about this phenomenon.